Análise da resposta hemodinâmica imediata da aplicação do laser de baixa intensidade em gestantes hipertensas e normotensas - Madi, Otavio (2024)
Background: Serious complications of systemic arterial hypertension (SAH) and preeclampsia (PE) in pregnant women may indicate the interruption of pregnancy and childbirth. Low-level laser therapy (LLLT) was applied in spontaneous hypertensive rats and in SAH patients, results indicated hemodynamics changes. Due to a reduction of the oxidative stress parameters by acting on endothelial dysfunction, that is etiopatogenic base of SAH and PE. Objective: To evaluate immediate response post low-level laser therapy in hypertensive and normotensive pregnant women and possible fetal repercussion. Methodology: Twenty patients of pregnant women (HPW) divided in two groups (normotensive and hypertensive) into 2 phases. All patients rested for 15min between the 2 phases. The hemodynamic parameters with HDI was measured. First phase - placebo (laser off) results of average heart rate, systolic, diastolic and mean blood pressure besides systemic vascular resistance were recorded. Second phase – (laser on) LLLT irradiated through intranasal in the following applied parameters: wavelength (λ) = 808nm, power = 100mW, time = 120s, fluence = 60J/cm2, energy/AP = 6J, total energy = 12J, intensity = 500 mW/cm2, spot size = 0.2 cm2. Cardiotocography monitored the fetuses throughout the entire procedure. Results: The systemic vascular resistance and therefore the systolic, diastolic and mean blood pressure suffered a significant decrease statistically, succeeding photobiomodulation in hypertensive pregnant women. In normotensive pregnant women, such effects were not observed. Considering cardiotocography, no adverse effects of maternal and fetal repercussions were detected. Conclusions: Lasertherapy was able to diminish the systemic vascular resistance and decrease the systemic blood pressure in hypertensive pregnant women. Lasertherapy indicated no side effect on normotensive and hypertensive pregnant women. Thus, the Laser did not produce harm to the fetus, moreover signalized a favorable and feasible fetal repercussion.